PHENOMENOLOGICAL REFLECTION OF LIFECREATION OF PERSONALITY AS SPIRITUAL CREATURE - Климишин, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article has author’s point of view on the nature of human from the position of Christian Psychology. The understanding of human as spiritual creature through the prism of ontological, social-psychological, cultural spectra of its nature is proved.